The Ability of European Convention on Human Rights in Preventing Gross Violations of Human Rights - Murat Tumay (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
The humanity faced very tragic consequences of war and other cruel teratments from state practices in history. To minimise the human rights violations, international community started to construct human rights protection systems. United Nations was established in 1945. The Universal Declaration of Human Rights was followed by main human rights protection treaties and monitoring systems established by those treaties. The European Convention on Human Rights was adopted on 4 November 1950 and entered into force on 3 September 1953. It’s the first international legally binding human rights treaty. The human rights protection system of European Convention is unique comparing with other international treaties. It is the first international system that provides individuals with right to complaint the state for violation of their human rights guaranteed in the Convention. It includes “international common law” feature and also it is self-referential regime. Because of its case law, Court is bound by their previous jurisprudence. This is its common law future. The Council of Europe bodies work independently from courts and legal systems of states` parties. Strasbourg is not appeal court of states parties; it interprets their domestic law and practise only in terms of compatibility with the Convention. The European Convention on Human Rights and its supervisory system have made considerable contributions to the whole human rights development in the world. The question in this study that does the Convention has the effective mechanism to combat with gross human rights violations. Gross and systematic violations are not common in the states parties of the Convention during the last four decades.It is a common view that there is no place for gross violations in so-called democracies of Western Europe. Such practices are confined to dictatorial regimes in other parts of the world. But somehow if gross and mass human rights violations occur in a member state to Convention, have the Convention and its implementation mechanism ability to fight with such violations?